E-cadherin/catenin complex status in solid pseudopapillary tumor of the pancreas. - El-Bahrawy, M; Rowan, A; Horncastle, D; Tomlinson, I; Theis, B; Russell, R; Stamp, G (2008)
Solid pseudopapillary tumor (SPT) of the pancreas is an uncommon neoplasm of uncertain lineage. They have been shown to express nuclear beta-catenin believed to be due to mutations of the beta-catenin gene. The aim of this study was to investigate the status of the E-cadherin/catenin complex in SPTs. We studied the expression of 4 principal members of the E-cadherin/catenin complex using immunohistochemistry and the E-cadherin gene status by screening all exons of the gene for mutations, in 6 cases of SPT. In addition to the nuclear localization of beta-catenin, we found nuclear localization of E-cadherin in all tumors with complete absence of membranous and cytoplasmic localization. Nuclear localization of E-cadherin was independent of beta-catenin. No mutations were identified in the E-cadherin gene in any of the tumors. Ten cases of pancreatic adenocarcinomas and 15 neuroendocrine tumors were studied as well for comparison. The reported changes in the expression of the principal members of the E-cadherin/catenin complex were unique to SPTs. Our study shows abnormalities in the expression of 4 principal members of the E-cadherin/catenin complex in SPTs, which may help to explain the discohesive nature of the cells and the cystic changes in these tumors, and provide additional diagnostic features.